OPTIMISING SALES THROUGH SOCIAL MEDIA AT THE TENUN IKAT ATBM KODOK NGOREK 2 - Dicka Dea, Sislindia; Widodo, Moch. Wahyu (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This research aims to analyse the digital marketing strategy through social media currently implemented by Tenun Ikat ATBM Kodok Ngorek 2, to identify the barriers faced by Tenun Ikat ATBM Kodok Ngorek 2 in using social media as a promotional and marketing tool, and to provide recommendations for strategies to optimise the use of social media to increase sales of Tenun Ikat ATBM Kodok Ngorek 2 products. Design/Methode/Approach : This research uses descriptive research with qualitative methods. The types of data sources used in this research are primary data and secondary data. The data collection technique of this research is observation, interview, documentation with purposive sampling technique in selecting informants. The data analysis technique used in this research is data reduction, data presentation, inference. The data validity test technique used in this research is source triangulation. Research Finding : The results showed that Tenun Ikat ATBM Kodok Ngorek 2 has used social media, especially Instagram and WhatsApp, to market its products, but the strategy used is still not optimal. The content uploaded tends to be monotonous, focusing on product photos and production processes without creative visual elements. The obstacles include the lack of varied content, the absence of a dedicated social media management team and the limited platforms used. To overcome this, it is recommended to diversify content, use TikTok, create a social media team and present complete product information. By implementing these strategies, Tenun Ikat ATBM Kodok Ngorek 2 can increase audience engagement, expand market reach and build a stronger brand in the digital age. Theoretical contribution/Originality : This research contributes to the MSME digital marketing literature by exploring social media optimisation strategies for distinctive handicraft products such as Tenun Ikat ATBM Kodok Ngorek. The novelty of this research lies in the integration of creative content diversification and new social media platforms (such as TikTok) in an effort to improve the competitiveness and visibility of MSME products. Practitionel/Policy implication : This research provides practical guidance for MSMEs on how to use social media more effectively, including setting up a dedicated team and presenting complete information about their products. Research limitation : This research only focuses on two social media platforms (Instagram and WhatsApp) and one case study (Tenun Ikat ATBM Kodok Ngorek). The generalisability of the research findings for other MSMEs needs to be assessed through further studies with a wider platform coverage.